The Analysis of Determinants of Going Concern Audit Opinion in Manufacturing Companies Listed on The Indonesia Stock Exchange (IDX) - I Nyoman Kusuma Adnyana Mahaputra; Putu Novia Hapsari Ardianti; Ni Putu Putri Anjani (Journal of International Conference Proceedings, 2023)
The resilience of Indonesian companies and the economy is being tested by the Covid-19 pandemic. Many companies are struggling to survive and are looking for ways to continue their business. If the auditor finds any doubts about the company's survival, the auditor will issue a going concern audit opinion. This research was conducted with the aim of knowing the effect of Profitability, Liquidity, Company Size, Previous Audit Opinion, and Public Accounting Firm Size on Going Concern Audit Opinions of Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) for 2018-2021. This study uses secondary data obtained from annual reports and independent auditors' reports published on the official website of the Indonesia Stock Exchange (www.idx.co.id). The sample for this research is a manufacturing company listed on the Indonesia Stock Exchange in 2018-2021. Sampling in this study used a purposive sampling technique and the samples obtained were 73 companies. The data analysis technique used in this study is logistic regression analysis. The results of this study concluded that the profitability and size of the public accounting firm had a negative effect on the going-concern audit opinion. While liquidity and company size have no effect on going concern audit opinion. And the previous audit opinion positively affects the going concern audit opinion.